Malnutrition and gender disparities in the Eastern Mediterranean Region: The need for action - Jabbour, Jana; Khalil, Merette; Ronzoni, Anna Rita; Mabry, Ruth; Al-Jawaldeh, Ayoub; El-Adawy, Maha; Sakr, Hala (Frontiers in Nutrition, 2023)
Malnutrition takes a heavy toll on the populations of the Eastern Mediterranean Region (EMR), with gender related socioeconomic risk factors impacting undernutrition and obesity in both women and men. This perspective article, a derivative of a report by the World Health Organization, reviews the scientific literature on the effect of gender on malnutrition related outcomes in the EMR. Results revealed that biological and gender-related socioeconomic risk factors play a role for undernutrition and obesity in both women and men. Malnutrition can be negatively influenced by gender-biased cultural standards, habits, structural determinants, differential exposures, and health system gaps. This can result, for example, in women tending to focus on familial and household related needs, at the expense of their own health and physical mobility and on suffering more food insecurity, undernutrition, micronutrient deficiencies and obesity compared to men in the EMR. Conflict and crisis situations negatively affect both genders, but generally put women at a higher risk of adverse. Women’s socially limited autonomy in mobility is also an obstacle to access to health services in the EMR, including those related to nutrition. Multi-level approaches are needed to address gender issues to enable a more equitable distribution of resources and reduce the impact of malnutrition in the EMR.